EXAMINATION OF THE SYSTEM OF CONTINUOUS DIAGNOSIS AND FORECASTING OF MECHANICAL CONDITION OF TRACTORS AND OTHER FARM MACHINERY - Gabitov, Ildar; Insafuddinov, Samat; Ivanov, Yurij; Yunusbaev, Nail; Abdrazakov, Farid; Farhutdinov, Timur (Journal of Applied Engineering Science, 2020)
The paper presents an experimental system of continuous diagnosis and forecasting of the technical condition oftractors and other farm machinery. The system has both advantages and disadvantages. The experiments provedthat the imprecisions of the existing Russian domestic sensors and actuating devices are several times higher thanthe permissible errors of engine parameters and its process conditions, which were determined based on the analysisof the engine adjusting characteristics. The system we offer allows to expand signifi cantly the possibilities of theuse of the agricultural aggregates, machines and implements and to reduce the down and repair time. The existingmicroprocessor side system signifi cantly simplifi es the synthesis of the proposed system and expands the technologicalcapabilities. It allows to make automatic diagnosis of the technical condition of the machine-tractor aggregate(MTA) and makes it possible to obtain information on the need for motor maintenance (MM) if necessary. The optionof voice information makes the operator work easier and thereby increases the effi ciency of MTA fi eld work.
Keywords: tractor; machinery; Agriculture